SARS-CoV-2 variants and ending the COVID-19 pandemic - Fontanet, Arnaud; Autran, Brigitte; Lina, Bruno; Kieny, Marie Paule; Karim, Salim S Abdool; Sridhar, Devi (The Lancet (British edition), 2021)
[...]the end of the pandemic is only possible when vaccines that are effective against circulating variants are distributed equitably across the world. [...]for surveillance of the circulation of SARS-CoV-2 variants, sharing of variant-specific PCR primers could help to monitor their spread, particularly in resource-limited countries. [...]a central repository of samples of sera and cells from individuals with past infection or past immunisation with available COVID-19 vaccines should be established for seroneutralisation and cellular immunity functional testing against newly discovered variants.